Accumulation ofLow Density Lipoprotein (LDL) in Diseased Artery - Mohd Razmi, Nurulain Amelia (Universiti Teknologi PETRONAS, 2012)
A cardiovascular disease such as heart attacks, strokes and hypertension is the primary cause of deaths around the world. The atherosclerosis progression is where the artery becomes hardening due to accumulation of bad cholesterol also known as low density lipoprotein (LDL). This project is modeled and simulatedby using the ANSYS 14.0 software package. The stenosis artery with 30% reduction with total length is 22 mm and 2 mm of diameter aligned in position x-axis. Then, stenosis tube is modeled and being put in meshing before setting up the solver. The solver is setting up with Spalart Allmaras model in order to study the blood flow behavior. The study were involved the characterization of blood flow under steady state mode and the inlet velocities were 0.18 m/s, 0.2 m/s, 0.3 m/s, 0.4 m/s and 0.5 m/s. The Discrete Phase Model is used to consider the LDL particle motion in blood flow and the LDL size that put into consideration during the study was 1 um, 3 \im and 5 um. The finite volume method is used to solve Navier stoke (NS) equation as governing equation as well as the particle motion equation which it is demonstrated the LDL particle movement in the stenosis artery. From the studies, it has been found that high velocity will create the recirculation region. Thus, LDL particle will travel longer than low velocity, which means it long residence time of LDL particle. Thus, the chance of LDL accumulation near the artery wall is high. The study also shows that the size of lipid particle effect the atherosclerosis progression significantly. It can be said that, big size of LDL give a great impact to the atherosclerosis progression. The finding of this project has proved that parameters, LDL residence time and LDL size have a great contribution toward the atherosclerosis progression. But, mass transfer of LDL did not take into account and the study of it is considerable to be employed in a future.